Neurometabolic signatures of gastrointestinal symptoms in the insula of Crohn’s disease patients: explorative findings from a 7T MRS study - Berthold, Marja-Lisa; Hartmann, Hanna; Farrher, Ezequiel; Zimmermann, Markus; Jaeger, Julius; Shah, N. Jon; Schneider, Kai Markus; Neuner, Irene; Rajkumar, Ravichandran (Frontiers in Human Neuroscience, 2025)
BackgroundThe bidirectional communication between the brain and gut in Crohn’s disease is increasingly acknowledged, highlighting how gut inflammation can influence brain function and psychological health, and vice versa, through the gut-brain axis. The insula is critical for processing pain, its emotional evaluation, and for regulating neurometabolites involved in these processes. The role of insular neurometabolites in gastrointestinal symptoms, particularly pain, in Crohn’s disease patients, however, is not well-understood, highlighting the need for further investigation. Therefore, this study aims to enhance our understanding of the connection between Crohn’s disease and brain function by investigating neurometabolic profiles in the insula of patients with Crohn’s disease.MethodsIn this study, 7 Tesla proton magnetic resonance spectroscopy (1H-MRS) was utilized to examine the left insular cortex in 14 individuals with Crohn’s disease and 14 age- and gender-matched healthy controls during resting state. Participants also completed neuropsychological evaluations, including the Gastrointestinal Symptom Rating Scale (GSRS) and the Pain Catastrophizing Scale (PCS).ResultsNo significant differences were found in the absolute concentrations of insular neurometabolites between Crohn’s disease patients and healthy controls. However, in patients with Crohn’s disease, GSRS scores were negatively correlated with the neurometabolites aspartate (Asp) and N-acetylaspartylglutamate (NAAG) in the insula. Furthermore, significant positive correlations were observed between scores on the PCS magnification subscale and concentrations of neurometabolites—namely glutamine (Gln) and the combined glutamate and glutamine signal (Glx) —as measured by (1H-MRS).ConclusionThe neurometabolic alterations observed in the insular cortex of Crohn’s disease patients suggest increased insular activity, which may enhance interoceptive awareness and pain sensitivity, potentially contributing to heightened pain catastrophizing.